1998
DOI: 10.1097/00006454-199803000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis evaluations in hospitalized infants with bronchiolitis

Abstract: Temperature was not a predictor of sepsis evaluation. Infants with respiratory distress and normal chest roentgenogram were more likely to receive sepsis evaluations; those with recognized typical bronchiolitis and those > 28 days of age were less likely. Risk of serious bacterial infection is low; the costs of a sepsis evaluation outweigh the benefits in infants with obvious bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 24 publications
1
64
1
1
Order By: Relevance
“…Exceptions have been noted in the literature and will certainly occur at a low rate. For example Antonow et al 11 reported on 282 infants Ͻ60 days of age who were hospitalized for bronchiolitis. Five (1.5%) of the infants had a serious bacterial infection with 3 urinary tract infections, 1 pneumococcal bacteremia and 1 meningitis diagnosed by CSF pleocytosis with sterile blood and cerebrospinal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions have been noted in the literature and will certainly occur at a low rate. For example Antonow et al 11 reported on 282 infants Ͻ60 days of age who were hospitalized for bronchiolitis. Five (1.5%) of the infants had a serious bacterial infection with 3 urinary tract infections, 1 pneumococcal bacteremia and 1 meningitis diagnosed by CSF pleocytosis with sterile blood and cerebrospinal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…4 Concomitant and secondary bacterial infections in patients with viral diseases are known to occur. [5][6][7][8][9][10][11][12][13][14][15][16][17] These bacterial infections tend to be focal, mainly pneumonia or acute otitis media. 11,12,14 Much of the existing data pertain to children 3 months or older.…”
mentioning
confidence: 99%
“…11,12,14 Much of the existing data pertain to children 3 months or older. [5][6][7][8] Currently, there is no consensus on the necessity of such a workup in the very young infant when there is certainty of viral, specifically RSV, infection. This is a retrospective cohort study ascertaining the incidence, determinants, and outcome of sepsis workup in febrile infants aged 0-90 days infected with RSV.…”
mentioning
confidence: 99%
“…As reported in Antonow et al [112], among infants hospitalized with bronchiolitis, those who underwent sepsis evaluation had a hospitalization cost of $4,507 and a hospital length of stay of 3.4 days on average. In contrast, the others had a lower hospitalization cost of $2,998 and a shorter hospital length of stay of 2.8 days on average.…”
Section: Predicting Serious Bacterial Infectionmentioning
confidence: 67%
“…Antonow et al [112], 49.6% of infants who are younger than 60 days and hospitalized with bronchiolitis receive sepsis evaluation. However, most of these evaluations are unnecessary.…”
Section: Predicting Serious Bacterial Infectionmentioning
confidence: 99%